Music, emotions and investment-related risk-taking behaviour - Goh, Shaw Heng; Goh, Kah Hong (2019)
The aim of this study is to find out whether happy and sad music will induce emotion respectively, and whether different induced emotion will cause any difference in making investment-related risk making decision. The time taken for different induced emotion to make risky decision is also recorded. In this study, 120 participants from Universiti Tunku Abdul Rahman are recruited from several faculties. They were randomly assigned into experimental conditions (happy or sad music) and control (no music) and had to answer or perform (type of tasks) as part of the quasi-experiment. The results in this study shows that happy music can induce happy emotion and sad emotion can induce sad emotion. This found that induced emotion did not significantly affect risky decision making. However, participants with sad induced emotion use longer time to make risky investment decision than participants with induced happy emotion. Negative emotion can slow down decision making process, while happy emotion can cause shorter information processing further process. Further studies are required to investigate the effect of emotion in making risky decision. The present study can contribute in clinical study as a screening tool to identify the impulsive behaviour and also increase the understanding of investors in investment behaviour.